Expression Level of ADAMTS1 in Granulosa Cells of PCOS Patients Is Related to Granulosa Cell Function, Oocyte Quality, and Embryo Development - Yang, Guang; Yao, Guidong; Xu, Ziwen; Fan, Huiying; Liu, Xingui; He, Jiahuan; Kong, Yue; Kong, Deqi; Bai, Yucheng; He, Qina; Zhang, Tongwei; Zhang, Junya; et al. (Frontiers in Cell and Developmental Biology, 2021)
A disintegrin and metalloproteinase with thrombospondin motifs 1 (ADAMTS1) is an extracellular matrix metalloproteinase that plays an important role in the process of ovulation. According to previous studies, the expression level of ADAMTS1 in the granulosa cells of PCOS patients and the mechanism for regulating oocyte quality and embryonic development potential are still unclear. Our research clarified that ADAMTS1 was significantly increased in granulosa cells of PCOS patients as compared to ovulatory controls . After silencing ADAMTS1 in granulosa cells, cell proliferation and E2 secretion were significantly inhibited, which may be related to the down-regulation of B-cell lymphoma 2 (Bcl2) family genes and key genes involved in E2 synthesis. Through retrospective analysis of the clinical data, it was found that the expression level of ADAMTS1 was significantly positively correlated to the oocyte maturation rate and good-quality embryo rate in PCOS patients. The downregulation of ADAMTS1 in primary granulosa cells lead to the changes in the expression of marker genes for oocyte and embryonic quality. By using immunofluorescence staining, it was found ADAMTS1 was expressed in various stages of pre-implantation embryo but its expression level gradually decreases with the development of the embryo. In addition, the silence of ADAMTS1 in 3PN zygotes significantly prolonged the development time of the zygote to the morula stage. This is, to our knowledge, the first time to explored the mechanism by which ADAMST1 is involved in affecting the quality of oocytes and embryonic development potential, which will provide new evidence for further understanding of the follicular microenvironment and embryo development.